Prevalence of Early Vascular Aging Syndrome in Men Working Under Noise Exposure - M. D. Rudoi (SINAPS LLC, 2024)
Noise can be one of the factors provoking the premature development of changes in the artery wall associated with age. Aim: to assess the stiffness of the vascular wall and the prevalence of early vascular aging syndrome in men of working age, depending on contact with noise, smoking status and the presence of hypertension. Materials and methods. 148 men worked in noise and 90 men for whom the level of all harmful production factors in the workplace did not exceed the permissible standards were examined. The average age of the examined patients was 41.6 ± 9.9 years, 133 people (55.9 %) were smokers, 43 people (18.1 %) were obese, 47 people (19.7 %) had a complicated heredity, 132 people (55.5 %) had hypercholesterolemia, and 37 people (15.5 %) suffered from arterial hypertension (AH). Each of the patients suffering from hypertension received antihypertensive therapy. There were no significant differences in the structure of antihypertensive therapy in the compared groups of patients. The groups of surveyed were comparable in age, body mass index, prevalence of smoking, obesity and hypertension. All patients underwent volumetric sphygmography according to the standard procedure in the morning on the VaSera 1500N device (FukudaDenshi, Japan), the device automatically determined the cardio-ankle vascular index on the right and left (R/L - CAVI), the estimated age of the arteries. The syndrome of early vascular aging (EVA syndrome) was considered to be a clinical condition associated with an excess of the estimated age of the arteries of the patient's passport age by 4 years or more (VaSera criteria). Results and discussion. After exclusion of smokers and hypertensive patients from the analysis and correction for age, the vascular wall stiffness index on the right and left in the main group of patients significantly exceeded the indicated indicator in the comparison group. R - CAVI was 7.2 [6.9; 7.9] and 7.05 [6.05; 7.45], respectively, p=0.02; L - CAVI was 7.3 [7.0; 7.9] and 6.85 [6.05; 7.65], respectively, p =0.007. In the group of people working in noise, the estimated age of the arteries significantly exceeded the passport age (p=0.004), whereas in the control group these indicators were comparable (p=0.27). The prevalence of EVA syndrome in the main group of patients was 14 cases (27.5 %), which was 8.6 times higher than the prevalence of EVA syndrome in the comparison group - 1 case (3.2 %); p=0.004. The comparability of the patient groups according to the main cardiovascular risk factors and the exclusion criteria from the study suggested that the identified changes in the state of the vascular wall are associated with the effects of noise on the body of the examined. Conclusion. Noise can be a factor that accelerates vascular aging. It is necessary to monitor the state of the cardiovascular system in persons working in noise.